2021
DOI: 10.1007/s11695-021-05286-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Emergency Department Visits and Readmissions After Laparoscopic Roux-en-Y Gastric Bypass: a Systematic Review

Abstract: Purpose There is considerable evidence on short-term outcomes after laparoscopic Roux-en-Y gastric bypass (LRYGB), but data on long-term outcome is scarce, especially on postoperative emergency department (ED) visits and readmissions. We aim to systematically review evidence on the incidence, indications, and risk factors of ED visits and readmissions beyond 30 days after LRYGB. Materials and Methods A systematic search in PubMed, Scopus, Embase.com, Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
0
12
0
1
Order By: Relevance
“… 13–15 However, long-term studies have shown that RYGB is also associated with gastrointestinal ulcers, dumping syndrome and chronic nutritional deficiencies, which can result in high rates of hospitalisations and the need for repeat surgery. 16–18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 13–15 However, long-term studies have shown that RYGB is also associated with gastrointestinal ulcers, dumping syndrome and chronic nutritional deficiencies, which can result in high rates of hospitalisations and the need for repeat surgery. 16–18 …”
Section: Introductionmentioning
confidence: 99%
“…RYGB results in significant loss of body weight, improvement of hepatic steatosis and can treat hypertension and type 2 DM 13–15. However, long-term studies have shown that RYGB is also associated with gastrointestinal ulcers, dumping syndrome and chronic nutritional deficiencies, which can result in high rates of hospitalisations and the need for repeat surgery 16–18…”
Section: Introductionmentioning
confidence: 99%
“…Bariatric surgery leads to considerable long-term weight loss and remission of obesity-related comorbidities with an acceptable low 30-day complication rate [3]. However, abdominal complaints are a common problem in the long term, leading to high numbers of emergency department visits, readmissions, and outpatient clinic visits [4]. Well-known causes include anastomotic ulcers, internal herniation, and gallstone disease [4].…”
mentioning
confidence: 99%
“…However, abdominal complaints are a common problem in the long term, leading to high numbers of emergency department visits, readmissions, and outpatient clinic visits [4]. Well-known causes include anastomotic ulcers, internal herniation, and gallstone disease [4]. However, a significant part of chronic abdominal complaints after surgery remains unexplained [5,6].…”
mentioning
confidence: 99%
“…evidence and focus on abdominal pain after bariatric surgery [1]. In their systematic review, although incorporating limitations such as restricted long-term data availability, retrospective data, and data heterogeneity, they find indications of longterm emergency department visits and hospital admissions mostly for acute abdominal pain in close to one in three patients.…”
mentioning
confidence: 99%